One-third nerd - Choldenko, Gennifer, 1957- (Wendy Lamb Books, 2019)
Ten-year-old Liam and his two younger sisters, precocious third-grader Dakota and second-grader Izzy, who has Down syndrome, face the possibility of losing their beloved dog, Cupcake, who keeps urinating on their apartment's carpet.